La Qashamárquida: la mitología de Cajamarca y su deconstrucción simbólica a través de la representación artística desde una mirada descolonial - Tejada Valdiviezo, Diego Rodrigo (Pontificia Universidad Católica del Perú, 2025)
The artistic project focuses on the mythology-willakuy of Cajamarca as a means to explore and deconstruct the consequences of colonialism. Drawing on theories from authors such as Aníbal Quijano, Rita Segato, and Silvia Rivera Cusicanqui, the research analyzes how coloniality impacted social, cultural, and gender structures, leading to the perception of non-Western mythologies as “primitive” thought, stripped of their complexity.. Through art, the project seeks to reconstruct and reinterpret local myths-willakuy confronting them with hegemonic Western narratives and highlighting their potential to create new ways of thinking. The creative process includes the symbolic analysis of Cajamarcan myths-willakuy, the reconstruction of images and narratives from a descolonial perspective, and the creation of artistic works that challenge power structures based on racism and gender violence. These works integrate pictorial, poetic and installation elements that promote critical reflection and active viewer participation. Methodologically, the project combines theoretical research, artistic analysis, and the pictorial materialization of myths-willakuythrough a qualitative strategy that seeks to highlight the relevance of non-Western mythologies as agents of cultural resistance.

El proyecto artístico se enfoca en la mitología-willakuy de Cajamarca como un medio para explorar y deconstruir las consecuencias del colonialismo. Basándose en teorías de autores como Aníbal Quijano, Rita Segato y Silvia Rivera Cusicanqui, la investigación analiza cómo la colonialidad impactó en las estructuras sociales, culturales y de género de modo que las mitologías no occidentales son percibidas como pensamientos “primitivos” al haber sido despojadas de su complejidad. A través del arte, el proyecto busca reconstruir y reinterpretar los mitos-willakuy locales enfrentándolos a las narrativas hegemónicas occidentales y resaltando su potencial para crear un nuevo pensamiento. El proceso creativo incluye el análisis simbólico de mitos-willakuy cajamarquinos, la reconstrucción de imágenes y narrativas desde un enfoque descolonial, y la creación de obras artísticas que cuestionan estructuras de poder basadas en racismo y violencia de género. Estas obras integran elementos pictóricos, poéticos y de instalación que promueven la reflexión crítica y la participación activa del espectador. Metodológicamente, el proyecto combina investigación teórica, análisis artístico y materialización pictórica de los mitos-willakuy mediante una estrategia cualitativa que busca resaltar la relevancia de las mitologías no occidentales como agentes de resistencia cultural.
The Qashamarquida: The Mythology of Cajamarca and Its Symbolic Deconstruction Through Artistic Representation from a Descolonial Perspective
Keywords: Myth-Willakuy; Descoloniality; Symbolism; Painting; Deconstruction; Mito-willakuy; Descolonialidad; Simbolismo; Pintura; Deconstrucción; https://purl.org/pe-repo/ocde/ford#6.04.01